Implementasi Komunikasi Multihop dengan Protokol HTTP pada Perancangan Sistem Monitoring Ketersediaan Tempat Duduk Pada Kafe - Ahmad Mustafa Kamal; Agung Setia Budi; Eko Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The current number of cafes, some of which have large spaces that cannot be monitored regularly by the cafe related to the availability of seats in the shop, so in one of the cases found in Kopi Daong in the city of Bogor, which was viral and was widely reported on TV because this cafe provides a place to enjoy a cup of coffee with a beautiful forest atmosphere. resulting in a boom in the number of visitors who come and the cafe cannot direct visitors to empty seats so visitors have to look for them themselves. In this case, a system is needed that can provide information regarding the availability of seats to make it easier for the cafe to direct visitors to empty places. This system utilizes a load-cell sensor as a data acquirer and nRF24L01 as a transceiver module and a website is made as the final output of the system so that it can provide information. In the implementation of this research, there are 2 transmitter server nodes that function as data acquirers as well as gateway nodes from 2 client transmitter nodes that function only to acquire data. All data is sent to the sink node and sent back to the database. Therefore, data transmission here uses a multihop mechanism. The results of the tests obtained have perfect accuracy, namely 100% in several test scenarios, namely related to node object recognition, output results on databases and websites, spacing between objects that have spacing scenarios ranging from 5m, 10m, 20m, and 40m. Then the routing of data communication and the successful delivery of data from the database and website side.